Modeling Of Wireless Energy Transfer Circuit And Implementation Of Wi-Tricity System Control Using Infrared And PIC Microcontroller - Najmiah Radiah, Mohamad; Azahari, Salleh; Nik Mohd Zarifie, Hashim; Mohamad Zoinol Abidin, Abd Aziz; Zahriladha, Zakaria (Engg Journals Publications, 2016)
A prototypes to prove and demonstrate the concept of Wireless Energy Transfer (WET) is proposed in this paper. The prototype is a simple structure consist of a transmitter as an electromagnetic resonator and a receiver to which the device to be powered is attached. It also implements with an ON/OFF control system using the Infrared (IR) module and Programmable Integrated Circuit (PIC) microcontroller. As a whole, experimental result proved that the distance between two coils is inversely directional to the level of current and voltage in the receiving coil. The strength of the magnetic field produced depends on the number of turns of both coils and input current plays an important role in determining the maximum distance between transmitter and receiver part. From the experiment, the receiver has the voltage of 10V for input current 3A, 5.213 V for input current 1A and 3.067 V for input current 500 mA at 0 distances. Besides that, the coil radius with 6 cm able to transmit 10 V to the receiver at zero distance while only 5.18V is transferred to the receiver for transmitter coil with radius 3 cm.